La orientación vocacional en los colegios públicos y privados de Lima: situación actual y propuesta de un programa de acción para la secundaria pública - Frisancho León, Augusto Emilio (2006)
This plan’s main objective is to determinate if the developing of vocational guide for students is going to be the same or different between private and public high schools from Lima Metropolitana. After a question paper application to a sample of 279 –male and female– just ending high school students, we found several differences between the two kinds of high schools. In addition of that finding, this plan proposes a Vocational guide plan direct to public high students, for the last three degrees in particular.